Unit V – Theory Of Equations
April May, 2006
1. I f O, A, B, C are the four point on a straight line such that the distance of A, B and C from
O are the roots of the equation
3 2
3 3 0 ax bx cx d + + + = . If B is the middle point of AC show
that
3 3
3 2 0 a d abc b ÷ + =
Ans . Let us assume , , are the roots of the equation
3 2
3 3 0 ax bx cx d + + + = and
, , OA OB OC = = =
According to the given condition ÷ = ÷
2 = + (1)
According to the property of roots
Now,
3b
a
÷
+ + = (2)
3c
a
+ + = (3)
d
a
÷
= (4)
From 2 and 3 we will have
3
3
b b
a a
÷
= ÷ ¬ = (5)
( )
3 3 c c
a a
+ + = ¬ + + =
From 1
2
2
3 3
2 2
c b c
a a a
÷  
+ = ¬ + =

\ .
2
2
3
2
c b
a a
¬ = ÷ (6)
Prepared by Mrityunjoy Dutta
again from 4 we have
d
a
÷
=
( )
d
a
÷
=
From 5 and 6 we have
2
2
3
2
b c b d
a a a a
  ÷ ÷  
÷ =
 
\ .
\ .
By solving above we will have
( )
2
2
3 2 ca b
b d
a
  ÷
=

\ .
Hence we will have
3 3
3 2 0 a d abc b ÷ + =
2. Solve by Cardan’s method of equation
3 2
3 3 0 x x ÷ + = .
Ans:
3 2
3 3 0 x x ÷ + = (1)
Here we can remove second termof equation (1) by diminishing its roots by
3
1
3 1
b
h
na
÷
= ÷ = ÷ =
×
We can diminished each root by 1 by synthetic division method
Hence the transformed equation is
3
3 1 0 y y ÷ + = (2)where 1 y x = ÷
Let
1/3 1/3
y p q = + be the solution of equation (2).
Prepared by Mrityunjoy Dutta
( )
3 1/3 1/3 1/3 1/3
3 y p q p q p q ¬ = + + +
3 1/3 1/3
3 y p q p q y ¬ = + +
3 1/3 1/3
3 ( ) 0 y p q y p q ¬ ÷ ÷ + = (3)
By comparing equation (2) and (3) we get
1/3 1/3
1, ( ) 1 p q p q ¬ = + =
1, ( ) 1 pq p q ¬ = + =
So, p and q are the roots of the equation
2
1 0 t t + + =
1 1 4 1 3
2 2
i
t
÷ ± ÷ ÷ ±
¬ = = .
So, let
1 3 1 3
,
2 2
i i
p q
÷ + ÷ ÷
= = .
So roots of given cubic equation (1) are
(i)
1/3 1/3
1/3 1/3
1 3 1 3
2 2
i i
p q
   
÷ + ÷ ÷
+ = +
 
 
\ . \ .
1/3 1/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
2 2 2 2
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
2
2cos
9
=
(ii)
1/3 1/3
1/3 2 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
wp wq
     
÷ + ÷ + ÷ ÷ ÷ ÷
+ = +
   
   
\ .\ . \ .\ .
4/3 4/3
1 3 1 3
2 2
i i
   
÷ + ÷ ÷
= +
 
 
\ . \ .
Prepared by Mrityunjoy Dutta
4/3 4/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
8 8 8 8
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
8
2cos
9
=
(iii)
1/3 1/3
2 1/3 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
w p wq
      
÷ ÷ ÷ + ÷ + ÷ ÷
+ = +
   
   
\ .\ . \ . \ .
1/3 1/3
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 3 3 3 3 3 3
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 9 9 3 3 9 9
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin
9 3 9 3 9 3 9 3
i i
           
= ÷ + ÷ + ÷ ÷ ÷
     
\ . \ . \ . \ . \ . \ .
4 4 4 4
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
4 4 14
2cos 2cos 2 2cos
9 9 9
 
= = ÷ =

\ .
So, roots of equation (2) are
2 8 14
2cos , 2cos , 2cos
9 9 9
Now, roots of given equation (1) are
2 8 14
1 2cos , 1 2cos , 1 2cos
9 9 9
+ + + (Ans)
3. Solve the equation by Ferrari’s method:
4 3 2
12 41 18 72 0 x x x x ÷ + ÷ ÷ = .
Ans:
4 3 2
12 41 18 72 0 x x x x ÷ + ÷ ÷ =
Let
4 3 2 2 2 2
( ) 12 41 18 72 ( 6 ) ( ) 0 f x x x x x x x mx n = ÷ + ÷ ÷ = ÷ + ÷ + = (1)
4 3 2 4 2 2 3 2 2 2 2
12 41 18 72 36 12 12 2 2 x x x x x x x x x mx mnx n ¬ ÷ + ÷ ÷ = + + ÷ ÷ + ÷ ÷ ÷
4 3 2 4 3 2 2 2 2
12 41 18 72 12 (36 2 ) ( 12 2 ) x x x x x x m x mn x n ¬ ÷ + ÷ ÷ = ÷ + + ÷ + ÷ ÷ + ÷
Equating the coefficients we get
Prepared by Mrityunjoy Dutta
2 2 2
(36 2 ) 41, ( 12 2 ) 18, 72 m mn n ¬ + ÷ = ÷ ÷ = ÷ ÷ = ÷
2 2 2
2 5, 9 6 , 72 m mn n ¬ = ÷ = ÷ = +
( )( ) ( )
2
2
2 5 72 9 6 ¬ ÷ + = ÷
3 2 2
2 144 5 360 81 36 108 0 ¬ + ÷ ÷ ÷ ÷ + =
3 2
2 41 252 441 0 ¬ ÷ + ÷ =
2
( 3)(2 35 147) 0 ¬ ÷ ÷ + =
21
2
3,7, ¬ =
By taking 3 1, 9 m n = ¬ = = ÷ equation (1) becomes
4 3 2 2 2 2
12 41 18 72 ( 6 3) ( 9) 0 x x x x x x x ¬ ÷ + ÷ ÷ = ÷ + ÷ ÷ =
2 2
( 6 3 9)( 6 3 9) 0 x x x x x x ¬ ÷ + + ÷ ÷ + ÷ + =
2 2
( 5 6)( 7 12) 0 x x x x ¬ ÷ ÷ ÷ + =
( 6)( 1)( 3)( 4) 0 x x x x ¬ ÷ + ÷ ÷ =
1,3,4,6 x ¬ = ÷ (Ans)
NovDec, 2006
4. Solve by Cardan’s method of equation
3 2
3 3 0 x x ÷ + = .
Ans:
3 2
3 3 0 x x ÷ + = (1)
Here we can remove second termof equation (1) by diminishing its roots by
3
1
3 1
b
h
na
÷
= ÷ = ÷ =
×
We can diminished each root by 1 by synthetic division method
Hence the transformed equation is
3
3 1 0 y y ÷ + = (2)where 1 y x = ÷
Prepared by Mrityunjoy Dutta
Let
1/3 1/3
y p q = + be the solution of equation (2).
( )
3 1/3 1/3 1/3 1/3
3 y p q p q p q ¬ = + + +
3 1/3 1/3
3 y p q p q y ¬ = + +
3 1/3 1/3
3 ( ) 0 y p q y p q ¬ ÷ ÷ + = (3)
By comparing equation (2) and (3) we get
1/3 1/3
1, ( ) 1 p q p q ¬ = + =
1, ( ) 1 pq p q ¬ = + =
So, p and q are the roots of the equation
2
1 0 t t + + =
1 1 4 1 3
2 2
i
t
÷ ± ÷ ÷ ±
¬ = = .
So, let
1 3 1 3
,
2 2
i i
p q
÷ + ÷ ÷
= = .
So roots of given cubic equation (1) are
(i)
1/3 1/3
1/3 1/3
1 3 1 3
2 2
i i
p q
   
÷ + ÷ ÷
+ = +
 
 
\ . \ .
1/3 1/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
2 2 2 2
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
2
2cos
9
=
(ii)
1/3 1/3
1/3 2 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
wp wq
     
÷ + ÷ + ÷ ÷ ÷ ÷
+ = +
   
   
\ .\ . \ .\ .
4/3 4/3
1 3 1 3
2 2
i i
   
÷ + ÷ ÷
= +
 
 
\ . \ .
Prepared by Mrityunjoy Dutta
4/3 4/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
8 8 8 8
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
8
2cos
9
=
(iii)
1/3 1/3
2 1/3 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
w p wq
      
÷ ÷ ÷ + ÷ + ÷ ÷
+ = +
   
   
\ .\ . \ . \ .
1/3 1/3
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 3 3 3 3 3 3
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 9 9 3 3 9 9
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin
9 3 9 3 9 3 9 3
i i
           
= ÷ + ÷ + ÷ ÷ ÷
     
\ . \ . \ . \ . \ . \ .
4 4 4 4
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
4 4 14
2cos 2cos 2 2cos
9 9 9
 
= = ÷ =

\ .
So, roots of equation (2) are
2 8 14
2cos , 2cos , 2cos
9 9 9
Now, roots of given equation (1) are
2 8 14
1 2cos , 1 2cos , 1 2cos
9 9 9
+ + + (Ans)
5. Solve the equation
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + = .
Ans:
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + =
The given equation is a reciprocal equation of odd degree having coefficient of terms
equidistance frombeginning and end.
So, 1 x= ÷ is its root.
4 3 2
( 1)(6 5 38 5 6) 0 x x x x x ¬ + ÷ ÷ ÷ + =
4 3 2
(6 5 38 5 6) 0 x x x x ¬ ÷ ÷ ÷ + =
Dividing by
2
x we get
Prepared by Mrityunjoy Dutta
2
2
5 6
6 5 38 0 x x
x x
¬ ÷ ÷ ÷ + =
2
2
1 1
6 5 38 0 x x
x x
   
¬ + ÷ + ÷ =
 
\ . \ .
2
1 1
6 2 5 38 0 x x
x x
 
   
¬ + ÷ ÷ + ÷ =

 

\ . \ .
\ .
( )
2
6 2 5 38 0 t t ¬ ÷ ÷ ÷ = where
1
x t
x
 
+ =

\ .
2
6 5 50 0 t t ¬ ÷ ÷ =
10 5
(3 10)(2 5) 0 ,
3 2
t t t ¬ ÷ + = ¬ = ÷
1 10 1 5
3 2
x and x
x x
¬ + = ¬ + = ÷
2 2
3 3 10 2 2 5 x x and x x ¬ + = ¬ + = ÷
2 2
3 10 3 0 2 5 2 0 x x and x x ¬ ÷ + = ¬ + + =
10 100 36 5 25 16
6 4
x and x
± ÷ ÷ ± ÷
¬ = ¬ =
10 8 5 3
6 4
x and x
± ÷ ±
¬ = ¬ =
1 1
3, 2,
2 2
x and x ¬ = ¬ = ÷ ÷
So, roots are
1 1
2, 1, , , 3
2 2
x ¬ = ÷ ÷ ÷ (Ans)
6. I f , , are the roots of the equation
3
0 x qx r + + = . Find the equation whose roots are
, ,
+ + + .
Ans: Given that , , are the roots of the equation
3
0 x qx r + + = .
Now, 0 + + = (1)
q + + = (2)
r = ÷ (3)
Now
2 2 2 2
( ) 2( ) 0 q q + + = + + ÷ + + = ÷ = ÷ (4)
Prepared by Mrityunjoy Dutta
Let , , A B C
= + = + = +
A B C
+ + = + + + + +
2 2 2 2 2 2
A B C
+ + +
¬ + + = + +
2 2 2 2 2 2
A B C
+ + +
¬ + + = + +
( ) ( ) ( )
2 2 2 2 2 2
A B C
+ + + + +
¬ + + =
( ) ( ) ( )
A B C
+ + + + +
¬ + + =
A B C
÷ ÷ ÷
¬ + + = as 0 + + =
3
3 A B C
÷
¬ + + = = ÷ (5)
AB BC CA
        
+ + = + + + + + + + +
     
\ .\ . \ .\ . \ .\ .
2 2 2 2 2 2 2 2 2 2 2 2
AB BC CA
         + + + + + +
¬ + + = + +
     
\ .\ . \ .\ . \ .\ .
( )( ) ( )( ) ( ) ( )
2 2 2 2 2 2 2 2 2 2 2 2
AB BC CA
+ + + + + +
¬ + + = + +
× × ×
( )( ) ( )( ) ( )( )
2 2 2 2 2 2
q q q q q q
AB BC CA
r r r
÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷
¬ + + = + +
÷ ÷ ÷
Prepared by Mrityunjoy Dutta
( )( ) ( )( ) ( )( )
2 2 2 2 2 2
q q q q q q
AB BC CA
r r r
+ + + + + +
¬ + + = + +
÷ ÷ ÷
( ) ( ) ( )
2 2 2 2 2 2 2 2 2 2 2 2 2 2 2
( ) ( ) ( ) q q q q q q
AB BC CA
r r r
+ + + + + + + + +
¬ + + = + +
÷ ÷ ÷
( ) ( ) ( )
2 3 2 2 2 2 3 2 2 2 2 3 2 2 2
q q q q q q q q q
AB BC CA
r r r
÷ ÷ + ÷ ÷ + ÷ ÷ +
¬ + + = + +
÷ ÷ ÷
( ) ( ) ( )
2 3 2 2 2 2 3 2 2 2 2 3 2 2 2
q q q q q q q q q
AB BC CA
r
÷ ÷ + + ÷ ÷ + + ÷ ÷ +
¬ + + =
÷
2 3 3 3 3 3 3 3
( )( ) ( ) q q q
AB BC CA
r
÷ + + ÷ + + + + +
¬ + + =
÷
( )
2 3 2
( ) ( ) 0 ( ) ( ) 3 ( ) q q q q r
AB BC CA
r
÷ ÷ ÷ × + + + + + ÷ + +
¬ + + =
÷
( )
3 4 2
3( )
( )
q q q q r q
AB BC CA
r r
÷ + ÷ ÷
¬ + + =
÷ ÷
3 4 2
2
2 3 q q q r
AB BC CA
r
÷ +
¬ + + = (6)
ABC
   
= + + +
  
\ .\ .\ .
2 2 2 2 2 2
ABC
    + + +
¬ =
  
\ .\ .\ .
2 2 2
q q q
ABC
    ÷ ÷ ÷
¬ =
  
\ .\ .\ .
3 2
2 2 2
( ) ( ) q q q
ABC
÷ + + + + + ÷
¬ =
Prepared by Mrityunjoy Dutta
3 2 3 2
2 2
0 q q r q q r
ABC
r r
÷ + +
¬ = =
Equation whose roots are A, B, C is
3 2
( ) ( ) 0 x A B C x AB BC CA x ABC ¬ ÷ + + + + + ÷ =
3 4 2 3 2
3 2
2 2
2 3
3 0
q q q r q q r
x x x
r r
÷ + +
¬ + + ÷ =
2 3 2 2 3 4 2 3 2
3 (2 3 ) ( ) 0 r x r x q q q r x q q r ¬ + + ÷ + ÷ + = (Ans)
7. Solve by Cardan’s method of equation
3 2
3 3 0 x x ÷ + = .
Ans:
3 2
3 3 0 x x ÷ + = (1)
Here we can remove second termof equation (1) by diminishing its roots by
3
1
3 1
b
h
na
÷
= ÷ = ÷ =
×
We can diminished each root by 1 by synthetic division method
Hence the transformed equation is
3
3 1 0 y y ÷ + = (2)where 1 y x = ÷
Let
1/3 1/3
y p q = + be the solution of equation (2).
( )
3 1/3 1/3 1/3 1/3
3 y p q p q p q ¬ = + + +
3 1/3 1/3
3 y p q p q y ¬ = + +
3 1/3 1/3
3 ( ) 0 y p q y p q ¬ ÷ ÷ + = (3)
Prepared by Mrityunjoy Dutta
By comparing equation (2) and (3) we get
1/3 1/3
1, ( ) 1 p q p q ¬ = + =
1, ( ) 1 pq p q ¬ = + =
So, p and q are the roots of the equation
2
1 0 t t + + =
1 1 4 1 3
2 2
i
t
÷ ± ÷ ÷ ±
¬ = = .
So, let
1 3 1 3
,
2 2
i i
p q
÷ + ÷ ÷
= = .
So roots of given cubic equation (1) are
(i)
1/3 1/3
1/3 1/3
1 3 1 3
2 2
i i
p q
   
÷ + ÷ ÷
+ = +
 
 
\ . \ .
1/3 1/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
2 2 2 2
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
2
2cos
9
=
(ii)
1/3 1/3
1/3 2 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
wp wq
     
÷ + ÷ + ÷ ÷ ÷ ÷
+ = +
   
   
\ .\ . \ .\ .
4/3 4/3
1 3 1 3
2 2
i i
   
÷ + ÷ ÷
= +
 
 
\ . \ .
4/3 4/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
8 8 8 8
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
8
2cos
9
=
Prepared by Mrityunjoy Dutta
(iii)
1/3 1/3
2 1/3 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
w p wq
      
÷ ÷ ÷ + ÷ + ÷ ÷
+ = +
   
   
\ .\ . \ . \ .
1/3 1/3
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 3 3 3 3 3 3
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 9 9 3 3 9 9
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin
9 3 9 3 9 3 9 3
i i
           
= ÷ + ÷ + ÷ ÷ ÷
     
\ . \ . \ . \ . \ . \ .
4 4 4 4
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
4 4 14
2cos 2cos 2 2cos
9 9 9
 
= = ÷ =

\ .
So, roots of equation (2) are
2 8 14
2cos , 2cos , 2cos
9 9 9
Now, roots of given equation (1) are
2 8 14
1 2cos , 1 2cos , 1 2cos
9 9 9
+ + + (Ans)
8. Solve the equation
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + = .
Ans:
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + =
The given equation is a reciprocal equation of odd degree having coefficient of terms
equidistance frombeginning and end.
So, 1 x= ÷ is its root.
4 3 2
( 1)(6 5 38 5 6) 0 x x x x x ¬ + ÷ ÷ ÷ + =
4 3 2
(6 5 38 5 6) 0 x x x x ¬ ÷ ÷ ÷ + =
Dividing by
2
x we get
2
2
5 6
6 5 38 0 x x
x x
¬ ÷ ÷ ÷ + =
2
2
1 1
6 5 38 0 x x
x x
   
¬ + ÷ + ÷ =
 
\ . \ .
Prepared by Mrityunjoy Dutta
2
1 1
6 2 5 38 0 x x
x x
 
   
¬ + ÷ ÷ + ÷ =

 

\ . \ .
\ .
( )
2
6 2 5 38 0 t t ¬ ÷ ÷ ÷ = where
1
x t
x
 
+ =

\ .
2
6 5 50 0 t t ¬ ÷ ÷ =
10 5
(3 10)(2 5) 0 ,
3 2
t t t ¬ ÷ + = ¬ = ÷
1 10 1 5
3 2
x and x
x x
¬ + = ¬ + = ÷
2 2
3 3 10 2 2 5 x x and x x ¬ + = ¬ + = ÷
2 2
3 10 3 0 2 5 2 0 x x and x x ¬ ÷ + = ¬ + + =
10 100 36 5 25 16
6 4
x and x
± ÷ ÷ ± ÷
¬ = ¬ =
10 8 5 3
6 4
x and x
± ÷ ±
¬ = ¬ =
1 1
3, 2,
2 2
x and x ¬ = ¬ = ÷ ÷
So, roots are
1 1
2, 1, , , 3
2 2
x ¬ = ÷ ÷ ÷ (Ans)
9. I f , , are the roots of the equation
3
0 x qx r + + = . Find the equation whose roots are
, ,
+ + + .
Ans: Given that , , are the roots of the equation
3
0 x qx r + + = .
Now, 0 + + = (1)
q + + = (2)
r = ÷ (3)
Now
2 2 2 2
( ) 2( ) 0 q q + + = + + ÷ + + = ÷ = ÷ (4)
Let , , A B C
= + = + = +
Prepared by Mrityunjoy Dutta
A B C
+ + = + + + + +
2 2 2 2 2 2
A B C
+ + +
¬ + + = + +
2 2 2 2 2 2
A B C
+ + +
¬ + + = + +
( ) ( ) ( )
2 2 2 2 2 2
A B C
+ + + + +
¬ + + =
( ) ( ) ( )
A B C
+ + + + +
¬ + + =
A B C
÷ ÷ ÷
¬ + + = as 0 + + =
3
3 A B C
÷
¬ + + = = ÷ (5)
AB BC CA
        
+ + = + + + + + + + +
     
\ .\ . \ .\ . \ .\ .
2 2 2 2 2 2 2 2 2 2 2 2
AB BC CA
         + + + + + +
¬ + + = + +
     
\ .\ . \ .\ . \ .\ .
( )( ) ( )( ) ( ) ( )
2 2 2 2 2 2 2 2 2 2 2 2
AB BC CA
+ + + + + +
¬ + + = + +
× × ×
( )( ) ( )( ) ( )( )
2 2 2 2 2 2
q q q q q q
AB BC CA
r r r
÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷ ÷
¬ + + = + +
÷ ÷ ÷
( )( ) ( )( ) ( )( )
2 2 2 2 2 2
q q q q q q
AB BC CA
r r r
+ + + + + +
¬ + + = + +
÷ ÷ ÷
Prepared by Mrityunjoy Dutta
( ) ( ) ( )
2 2 2 2 2 2 2 2 2 2 2 2 2 2 2
( ) ( ) ( ) q q q q q q
AB BC CA
r r r
+ + + + + + + + +
¬ + + = + +
÷ ÷ ÷
( ) ( ) ( )
2 3 2 2 2 2 3 2 2 2 2 3 2 2 2
q q q q q q q q q
AB BC CA
r r r
÷ ÷ + ÷ ÷ + ÷ ÷ +
¬ + + = + +
÷ ÷ ÷
( ) ( ) ( )
2 3 2 2 2 2 3 2 2 2 2 3 2 2 2
q q q q q q q q q
AB BC CA
r
÷ ÷ + + ÷ ÷ + + ÷ ÷ +
¬ + + =
÷
2 3 3 3 3 3 3 3
( )( ) ( ) q q q
AB BC CA
r
÷ + + ÷ + + + + +
¬ + + =
÷
( )
2 3 2
( ) ( ) 0 ( ) ( ) 3 ( ) q q q q r
AB BC CA
r
÷ ÷ ÷ × + + + + + ÷ + +
¬ + + =
÷
( )
3 4 2
3( )
( )
q q q q r q
AB BC CA
r r
÷ + ÷ ÷
¬ + + =
÷ ÷
3 4 2
2
2 3 q q q r
AB BC CA
r
÷ +
¬ + + = (6)
ABC
   
= + + +
  
\ .\ .\ .
2 2 2 2 2 2
ABC
    + + +
¬ =
  
\ .\ .\ .
2 2 2
q q q
ABC
    ÷ ÷ ÷
¬ =
  
\ .\ .\ .
3 2
2 2 2
( ) ( ) q q q
ABC
÷ + + + + + ÷
¬ =
3 2 3 2
2 2
0 q q r q q r
ABC
r r
÷ + +
¬ = =
Prepared by Mrityunjoy Dutta
Equation whose roots are A, B, C is
3 2
( ) ( ) 0 x A B C x AB BC CA x ABC ¬ ÷ + + + + + ÷ =
3 4 2 3 2
3 2
2 2
2 3
3 0
q q q r q q r
x x x
r r
÷ + +
¬ + + ÷ =
2 3 2 2 3 4 2 3 2
3 (2 3 ) ( ) 0 r x r x q q q r x q q r ¬ + + ÷ + ÷ + = (Ans)
MayJ une, 2007
10. Solve the equation by Ferrari’s method:
4 3 2
12 41 18 72 0 x x x x ÷ + ÷ ÷ = .
Ans:
4 3 2
12 41 18 72 0 x x x x ÷ + ÷ ÷ =
Let
4 3 2 2 2 2
( ) 12 41 18 72 ( 6 ) ( ) 0 f x x x x x x x mx n = ÷ + ÷ ÷ = ÷ + ÷ + = (1)
4 3 2 4 2 2 3 2 2 2 2
12 41 18 72 36 12 12 2 2 x x x x x x x x x mx mnx n ¬ ÷ + ÷ ÷ = + + ÷ ÷ + ÷ ÷ ÷
4 3 2 4 3 2 2 2 2
12 41 18 72 12 (36 2 ) ( 12 2 ) x x x x x x m x mn x n ¬ ÷ + ÷ ÷ = ÷ + + ÷ + ÷ ÷ + ÷
Equating the coefficients we get
2 2 2
(36 2 ) 41, ( 12 2 ) 18, 72 m mn n ¬ + ÷ = ÷ ÷ = ÷ ÷ = ÷
2 2 2
2 5, 9 6 , 72 m mn n ¬ = ÷ = ÷ = +
( )( ) ( )
2
2
2 5 72 9 6 ¬ ÷ + = ÷
3 2 2
2 144 5 360 81 36 108 0 ¬ + ÷ ÷ ÷ ÷ + =
3 2
2 41 252 441 0 ¬ ÷ + ÷ =
2
( 3)(2 35 147) 0 ¬ ÷ ÷ + =
21
2
3,7, ¬ =
By taking 3 1, 9 m n = ¬ = = ÷ equation (1) becomes
4 3 2 2 2 2
12 41 18 72 ( 6 3) ( 9) 0 x x x x x x x ¬ ÷ + ÷ ÷ = ÷ + ÷ ÷ =
2 2
( 6 3 9)( 6 3 9) 0 x x x x x x ¬ ÷ + + ÷ ÷ + ÷ + =
2 2
( 5 6)( 7 12) 0 x x x x ¬ ÷ ÷ ÷ + =
( 6)( 1)( 3)( 4) 0 x x x x ¬ ÷ + ÷ ÷ =
1,3,4,6 x ¬ = ÷ (Ans)
Prepared by Mrityunjoy Dutta
11. Solve by Cardan’s method of equation
3
15 126 0 x x ÷ ÷ = .
Ans:
3
15 126 0 x x ÷ ÷ =
Here the equation having terms involving
2
x termmissing.
Let
1/3 1/3
x p q = + be the solution of equation (1).
( )
3 1/3 1/3 1/3 1/3
3 x p q p q p q ¬ = + + +
3 1/3 1/3
3 x p q p q x ¬ = + +
3 1/3 1/3
3 ( ) 0 x p q x p q ¬ ÷ ÷ + = (2)
By comparing equation(1) and (2) we get
1/3 1/3
5, ( ) 126 p q p q ¬ = + = 125, ( ) 126 pq p q ¬ = + =
So, p and q are the roots of the equation
2
126 125 0 t t ÷ + =
( 1)( 125) 0 1,125 t t t ¬ ÷ ÷ = ¬ = . So, let p =1 and q =125.
So roots of given cubic equation (1) are
(i)
1/3 1/3
1 5 6 p q + = + =
(ii)
1/3 2 1/3
1 3 1 3 6 4 3
5 3 2 3
2 2 2
i i i
wp wq i
     
÷ + ÷ ÷ ÷ ÷
+ = + = = ÷ ÷
  
  
\ . \ . \ .
(iii)
2 1/3 1/3
1 3 1 3 6 4 3
5 3 2 3
2 2 2
i i i
w p wq i
     
÷ ÷ ÷ + ÷ +
+ = + = = ÷ +
  
  
\ . \ . \ .
So, roots are 6, 3 2 3, 3 2 3 i i ÷ ÷ ÷ + (Ans).
12. Solve
3 2
4 20 48 0 x x x ÷ ÷ + = given that the roots , are connected by the relation
2 0 + = .
Ans: Let , , are the roots of
3 2
4 20 48 0 x x x ÷ ÷ + = .
Given that 2 0 2 + = ¬ = ÷
Now, 4 + + = (1)
20 + + = ÷ (2)
48 = ÷ (3)
From(1) 2 4 4 ¬ ÷ + + = ¬ = + (4)
From(3) 2 . .(4 ) 48 ¬ ÷ + = ÷
3 2
4 24 ¬ + =
3 2
4 24 0 ¬ + ÷ =
2
( 2)( 6 12) 0 ¬ ÷ + + =
Prepared by Mrityunjoy Dutta
6 36 48
2, 2, 3 3
2
i
÷ ± ÷
¬ = = ÷ ±
So, 2 4, 6 = ¬ = ÷ =
So, roots are 4, 2, 6.
NovDec, 2007
13. Find the number of real roots the equation
3 2
x x 4x 4 0 ÷ + + = Ans: number of real roots the
equation
3 2
x x 4x 4 0 ÷ + + = are 3 , two positive roots and 1 negative roots.
14. Find the condition that the equation
3 2
x x 4x 4 0 p + + + = had roots , , which satisfy
1 0 + = .
Ans: Let , , are the roots of
3 2
0 x px qx r + + + = .
Given that 1 0 1 + = ¬ = ÷ (1)
Now, p + + = ÷ (2)
4 + + = (3)
4 = ÷ (4)
From(1) and (4) 4 ¬ = (4)
Putting the value of 4 = in the equation
3 2
0 x px qx r + + + = we will have
64 16 16 4 0 p + + + =
84 21
16 4
p
÷ ÷
= =
15. If , , are roots of the equation
3
0 x qx r + + = Find the equation whose roots are
( ) ( ) ( )
2 2 2
, , ÷ ÷ ÷
Ans: Let , , are the roots of
3
0 x qx r + + = …………………(1)
Now, 0 + + = (2)
q + + = (3)
r = ÷ (4)
Let ( )
2
y = ÷
( ) ( )
2 2
4 ¬ ÷ = + ÷
( ) ( )
2 2 4
¬ ÷ = + + ÷ ÷
Prepared by Mrityunjoy Dutta
( ) ( )
2 2 4
0
r
¬ ÷ = ÷ +
( ) ( )
2
2
4r
x
x
¬ ÷ = +
( )
2
4r
y x
x
¬ = +
3
4 0 x yx r ¬ ÷ + = ……………………………..(5)
Subtracting 4 from 1 we will have
( ) 3 0 q y x r + ÷ =
( )
3r
x
q y
=
+
………………..(6)
Put the value of x in the equation 1 we will have
3
3 3
0
r r
q r
q y q y
   
+ + =
 
+ +
\ . \ .
( ) ( )
2 3
3
27 3 0 r rq q y r q y + + + + =
( ) ( )
3 2 2 3 3 2 2
27 3 2 3 3 0 r rq q r rq r q r r q rq + + + + + + + =
3 3 3 2 2 3 4 3 2 2
27 3 3 6 3 3 0 r rq r q r q rq r r q r q + + + + + + + =
3 3 3 2 2 4
27 4 6 9 0 r rq r q r q r + + + + =
16. Solve by Cardan’s methods:
3
15 126 0 x x ÷ ÷ =
Ans:
3
15 126 0 x x ÷ ÷ =
Here the equation having terms involving
2
x termmissing.
Let
1/3 1/3
x p q = + be the solution of equation (1).
( )
3 1/3 1/3 1/3 1/3
3 x p q p q p q ¬ = + + +
3 1/3 1/3
3 x p q p q x ¬ = + +
3 1/3 1/3
3 ( ) 0 x p q x p q ¬ ÷ ÷ + = (2)
By comparing equation(1) and (2) we get
1/3 1/3
5, ( ) 126 p q p q ¬ = + = 125, ( ) 126 pq p q ¬ = + =
So, p and q are the roots of the equation
2
126 125 0 t t ÷ + =
( 1)( 125) 0 1,125 t t t ¬ ÷ ÷ = ¬ = . So, let p =1 and q =125.
So roots of given cubic equation (1) are
(i)
1/3 1/3
1 5 6 p q + = + =
Prepared by Mrityunjoy Dutta
(ii)
1/3 2 1/3
1 3 1 3 6 4 3
5 3 2 3
2 2 2
i i i
wp wq i
     
÷ + ÷ ÷ ÷ ÷
+ = + = = ÷ ÷
  
  
\ . \ . \ .
(iii)
2 1/3 1/3
1 3 1 3 6 4 3
5 3 2 3
2 2 2
i i i
w p wq i
     
÷ ÷ ÷ + ÷ +
+ = + = = ÷ +
  
  
\ . \ . \ .
So, roots are 6, 3 2 3, 3 2 3 i i ÷ ÷ ÷ + (Ans).
April May 2008
17. Form the equation whose roots are 1, 2, 3.
Ans .The equation will be ( )( )( ) 1 2 3 x x x ÷ ÷ ÷
( ) ( )( )
3 2
1 2 3 6 11 6 x x x x x x ÷ ÷ ÷ = ÷ + ÷
18. Solve the equation 2x
2
+x
2
7x6 =0 when the difference of two roots is 3.
Ans: Let , , are the roots of
3
+ ÷ ÷ =
2
2x x 7x 6 0 .
Given that 3 ÷ =  (1)
Now, 1/ 2 + + = ÷  (2)
7/ 2 + + = ÷  (3)
3 =  (4)
From(1) and (2) 2 7/ 2 + = ÷  (5)
From(4) and (1) . .(3 ) 3 ¬ + =  (6)
From(5) and (6)
7
2 .(3 ) 3
2
÷  
¬ ÷ + =

\ .
From
3 2
4 24 ¬ + =
3 2
4 24 0 ¬ + ÷ =
2
( 2)( 6 12) 0 ¬ ÷ + + =
6 36 48
2, 2, 3 3
2
i
÷ ± ÷
¬ = = ÷ ±
So, 2 4, 6 = ¬ = ÷ =
So, roots are 4, 2, 6.
19. If u,ß,y are the roots of the cubic
3 2
0 x px qx r ÷ + ÷ = find the equation whose roots are
Prepared by Mrityunjoy Dutta
1 1 1
, ,
+ + +
Ans. As , , are the roots of the cubic
3 2
0 x px qx r ÷ + ÷ = .
Here , , p q r + + = + + = =
Let root of the new equation is y, and according to the given condition
1 1 1 r
y y
x
+ +
= + ¬ = =
1 1 r r
y x
x y
+ +
= ¬ = and x is the root of the equation
3 2
0 x px qx r ÷ + ÷ =
3 2
1 1 1
0
r r r
p q r
y y y
      + + +
¬ ÷ + ÷ =
  
\ . \ . \ .
( ) ( ) ( )
3 2
2 3
1 1 1 0 r p r y q r y ry ¬ + ÷ + + + ÷ =
( ) ( ) ( )
3 2 2 2 3
1 3 3 1 2 1 0 r r r p r r y q r y ry ¬ + + + ÷ + + + + ÷ =
( ) ( ) ( )
3 2 2 3 2
1 1 2 1 3 3 0 ry q r y p r r y r r r ¬ ÷ + + ÷ + + + + + + =
Required equation will be
( ) ( ) ( )
3 2 2 3 2
1 1 2 1 3 3 0 ry q r y p r r y r r r ÷ + + + + ÷ + + + =
20.
Solve by Cardan’s methods:
3 2
9 +6x 1=0 x
Ans:
3 2
9 +6x 1=0 x
Here the equation having terms involving
2
x term. We can have another equation
1
= y
x
And by putting the value of y in the equation
3 2
9 +6x 1=0 x we will have
3 2
3
1 1
9 +6 1=0 y 6 9 0 y
y y
   
¬ ÷ ÷ =
 
\ . \ .
Here in the
3
y 6 9 0 y ÷ ÷ = ……………………………………………(2)
equation term involving
2
y is missing .
Let y u v = + be the solution of equation (2).
( )
3 3 3
3 y u v uv u v ¬ = + + +
3 3 3
3 y u v uvy ¬ = + +
( )
3 3 3
3 0 y uvy u v ¬ ÷ ÷ + = (2)
By comparing equation(1) and (2) we get
Prepared by Mrityunjoy Dutta
3 3
2, ( ) 9 uv u v ¬ = + = (3)
3 3 3 3 3 3
2, ( ) 9 8, ( ) 9 uv u v u v u v ¬ = + = ¬ = + =
So,
3
u and
3
v are the roots of the equation
2
9 8 0 t t ÷ + =
( )
2
9 8 0 ( 8) 1 t t t t ¬ ÷ + = = ÷ ÷ .
So, let
3
u =8 and
2
2,2 ,2 u w w = therefore from3 we will have
2
1, , v w w =
So roots of given cubic equation (1) are
(i) 2 1 3 u v + = + =
(ii)
2
1 3 1 3 3 3
2 2
2 2 2
i i i
u v w w
     
÷ + ÷ ÷ ÷ +
+ = + = + =
  
  
\ . \ . \ .
(iii)
2
1 3 1 3 3 3
2 2
2 2 2
i i i
u v w w
     
÷ ÷ ÷ + ÷ ÷
+ = + = + =
  
  
\ . \ . \ .
So, roots of the equation
3
y 6 9 0 y ÷ ÷ = are
3 3 3 3
3, ,
2 2
i i
   
÷ + ÷ ÷
 
 
\ . \ .
And roots of the equation
3 2
9 +6x 1=0 x are
1 1
1 3 3 3 3
, ,
3 2 2
i i
÷ ÷
   
÷ + ÷ ÷
 
 
\ . \ .
as
1
= y
x
Nov Dec 2008
21. From the equation whose roots are reciprocal of the roots of the equation
5 3 2
2 4 3 7 6 0 x x x x + ÷ + + =
Ans: The equation whose roots are reciprocal of the roots of the equation
5 3 2
2 4 3 7 6 0 x x x x + ÷ + + = is y
1
y
x
= by putting the value of y in the above equation we will have
( ) ( ) ( ) ( )
5 3 2
2 1/ 4 1/ 3 1/ 7 1/ 6 0 x x x x + ÷ + + =
4 3 5 2
6 7 3 4 2 0 x x x x + ÷ + + =
22. If
1 2 3
, , r r r are the root of the equation
3 2
2 3 1 0 x x kx ÷ + ÷ = find constant k if sum of
two roots is 1.
Let
1 2 3
, , r r r are the roots of
3 2
2 3 1 0 x x kx ÷ + ÷ = .
Given that
1 2
1 r r + =  (1)
Prepared by Mrityunjoy Dutta
Now,
1 2 3
3/ 2 r r r + + =  (2)
1 2 2 3 1 3
/ 2 rr r r rr k + + =  (3)
1 2 3
1/ 2 rr r =  (4)
From(1) and (2)
3
1/ 2 r =  (5)
From(5) and (4)
1 2
1 rr ¬ =  (6)
From(5) and (6)we can construct a quadratic equation that is
2
1 0 x x ÷ + =
By solving equation
2
1 0 x x ÷ + = we will have
2
4 1 3
2 2
b b ac i
x
a
÷ ± ÷ ±
= =
1 2 3
1 3 1 3
2
, , 1/ 2
2
i i
r r r = = =
+ ÷
23. Find the equation whose roots are the roots of x
4
+x
3
− 3x
2
−x +2 =û.each
diminished by 3.
Ans. The above equation can be solved by using synthetic division then we will have
3 y x = ÷
Let , , , are the roots of x
4
+x
3
−3x
2
− x +2 =û.
Now, 1 + + + = ÷  (1)
As roots are diminished by 3 therefore new root will be 3, 3, 3, 3 y = ÷ ÷ ÷ ÷
( ) ( ) ( ) ( ) 3 3 3 3 1 12 ÷ + ÷ + ÷ + ÷ = ÷ ÷
( ) ( ) ( ) ( ) 3 3 3 3 13 ÷ + ÷ + ÷ + ÷ = ÷
3 1 1 3 1 2
0 3 12 27 78
1 4 9 26 80
0 3 21 90
1 7 30 116
0 3 30
1 10 60
0 3
1 13
÷ ÷
Hence the new equation is
4 3 2
13 60 116 80 x x x x + + + +
Prepared by Mrityunjoy Dutta
24. Solve by Cardan’s method of equation
3
15 126 0 x x ÷ ÷ = .
Ans:
3
15 126 0 x x ÷ ÷ =
Here the equation having terms involving
2
x termmissing.
Let
1/3 1/3
x p q = + be the solution of equation (1).
( )
3 1/3 1/3 1/3 1/3
3 x p q p q p q ¬ = + + +
3 1/3 1/3
3 x p q p q x ¬ = + +
3 1/3 1/3
3 ( ) 0 x p q x p q ¬ ÷ ÷ + = (2)
By comparing equation(1) and (2) we get
1/3 1/3
5, ( ) 126 p q p q ¬ = + = 125, ( ) 126 pq p q ¬ = + =
So, p and q are the roots of the equation
2
126 125 0 t t ÷ + =
( 1)( 125) 0 1,125 t t t ¬ ÷ ÷ = ¬ = . So, let p =1 and q =125.
So roots of given cubic equation (1) are
(i)
1/3 1/3
1 5 6 p q + = + =
(ii)
1/3 2 1/3
1 3 1 3 6 4 3
5 3 2 3
2 2 2
i i i
wp wq i
     
÷ + ÷ ÷ ÷ ÷
+ = + = = ÷ ÷
  
  
\ . \ . \ .
(iii)
2 1/3 1/3
1 3 1 3 6 4 3
5 3 2 3
2 2 2
i i i
w p wq i
     
÷ ÷ ÷ + ÷ +
+ = + = = ÷ +
  
  
\ . \ . \ .
So, roots are 6, 3 2 3, 3 2 3 i i ÷ ÷ ÷ + (Ans).
MayJ une 2009
25. Write the relation between roots and coefficients of the equation.
1 2
0 1 2 1
.......... 0
n n n
n n
a x ax a x a x a
÷ ÷
÷
+ + + + + =
Ans: Let
1 2
, ,.........,
n
are roots of
1 2
0 1 2 1
.......... 0
n n n
n n
a x ax a x a x a
÷ ÷
÷
+ + + + + = .
Then
1
1
0
i
i n
a
a
s s
= ÷
¿
,
2 2
0
( 1)
i j
i j
a
a
=
= ÷
¿
3 3
0
( 1)
i j k
i j k
a
a
= =
= ÷
¿
Similarly,
1 2
0
......... ( 1)
n n
n
a
a
= ÷
26. I f , , are the roots of the cubic
3
0 x px q + + = . Show that
i.
5 5 5
5 + + = ÷
¿
Prepared by Mrityunjoy Dutta
ii.
2 5 3 4
3 5 =
¿ ¿ ¿ ¿
Ans: As , , are the roots of the cubic
3
0 x px q + + = .(1)
So, 0, , p q = = = ÷
¿ ¿
Now,
( )
2
2
2 0 2 2 p p = ÷ = ÷ = ÷
¿ ¿ ¿
.
2
2p ¬ = ÷
¿
(2)
As
3 3
0 3 0 3( ) 0 q = ¬ ÷ = ¬ ÷ ÷ =
¿ ¿ ¿
3
3q ¬ = ÷
¿
(3)
Let us multiply equation (1) by x we get
4 2
0 x px qx + + =
4 2
0 p q ¬ + + =
¿ ¿ ¿
4 2 2
( 2 ) (0) 2 p q p p q p ¬ = ÷ ÷ = ÷ ÷ ÷ =
¿ ¿ ¿
4 2
2p ¬ =
¿
(3)
(i)
5 5 5
5 + + = ÷
¿
Ans: Now by multiplying (1) by
2
x we get
5 3 2
0 x px qx + + =
5 3 2
0 p q + + =
¿ ¿ ¿
5 3 2
( 3 ) ( 2 ) 5 p q p q q p pq ¬ = ÷ ÷ = ÷ ÷ ÷ ÷ =
¿ ¿ ¿
(4)
5
5( ) q p ¬ = ÷ ÷
¿
5
5 ¬ = ÷
¿ ¿
5 5 5
5 ¬ + + = ÷
¿
(Proved)
(ii)
2 5 3 4
3 5 =
¿ ¿ ¿ ¿
Ans:
2 5 2
3 3.( 2 ).(5 ) 30 p pq p q = ÷ = ÷
¿ ¿
(5)
3 4 2 2
5 5( 3 )(2 ) 30 q p p q = ÷ = ÷
¿ ¿
(6)
From(5) and (6)
2 5 3 4
3 5 ¬ =
¿ ¿ ¿ ¿
(Proved)
27. Show that the equation
4 3 2
10 23 6 15 0 x x x x ÷ + ÷ ÷ = can be transformed into reciprocal
equation by diminishing the roots by 2. Hence solve the equation.
Ans: Let us diminished the roots of
4 3 2
10 23 6 15 0 x x x x ÷ + ÷ ÷ = (1) by 2.
Putting 2 2 y x x y = ÷ ¬ = +
By Using synthetic division method
Prepared by Mrityunjoy Dutta
The transformed equation is
4 3 2
2 13 2 1 0 y y y y ÷ ÷ ÷ + = (2)
Equation (2) is a reciprocal equation of even degree having coefficients of terms
equidistant fromthe beginning and end equal.
Dividing equation (2) by
2
y we get
2
2
2 1
2 13 0 y y
y y
÷ ÷ ÷ + =
2
2
1 1
2 13 0 y y
y y
   
¬ + ÷ + ÷ =
 
\ . \ .
Now putting
2 2
2
1 1
2 y z y z
y y
+ = ¬ + = ÷
2
2 2 13 0 z z ¬ ÷ ÷ ÷ =
2
2 15 0 ( 5)( 3) 0 z z z z ¬ ÷ ÷ = ¬ ÷ + =
3,5 z ¬ = ÷
1
3 y
y
¬ + = ÷
1
5 y
y
¬ + =
2
1 3 y y ¬ + = ÷
2
1 5 y y ¬ + =
2
3 1 0 y y ¬ + + =
2
5 1 0 y y ¬ ÷ + =
3 9 4
2
y
÷ ± ÷
¬ =
5 25 4
2
y
± ÷
¬ =
Prepared by Mrityunjoy Dutta
3 5
2
y
÷ ±
¬ =
5 21
2
y
±
¬ =
3 5 3 5 5 21 5 21
, , ,
2 2 2 2
y
÷ + ÷ ÷ + ÷
¬ =
So, solution for 2 x y = +
3 5 3 5 5 21 5 21
2, 2, 2, 2
2 2 2 2
x
÷ + ÷ ÷ + ÷
¬ = + + + +
1 5 1 5 9 21 9 21
, , ,
2 2 2 2
x
+ ÷ + ÷
¬ = (Ans)
28. Solve by Cardan’s method, the equation
3 2
27 54 198 73 0 x x x + + ÷ = .
Ans:
3 2
27 54 198 73 0 x x x + + ÷ =
3 2
22 73
2 0
3 27
x x x ¬ + + ÷ = (1)
Let us compare this equation with
3 2
0 ax bx cx d + + + =
Then
22 73
1, 2, ,
3 27
a b c d ¬ = = = = ÷
Putting
2 2
3 3
z ax b x x z = + = + ¬ = ÷ in (1) we get
3 2
2 2 22 2 73
2 0
3 3 3 3 27
z z z
     
¬ ÷ + ÷ + ÷ ÷ =
  
\ . \ . \ .
3 2 2
4 8 8 8 22 44 73
2 2 0
3 27 3 9 3 9 27
z z z z z z ¬ ÷ + ÷ + ÷ + + ÷ ÷ =
3
6 7 0 z z ¬ + ÷ = (2)
Now comparing with
3
3 0 z Hz G + + =
Where 2, 7 H G = = ÷
 
3 2
1 1 1
4 7 32 49 7 9 8
2 2 2
p G H G
(
(
= ÷ + + = + + = + =
¸ ¸
¸ ¸
So roots of given cubic equation (2) are
(i)
1/3
1/3
2
2 1
2
H
p
p
÷ = ÷ =
(ii)
1/3 2 2 2
1/3
2
2 2 2( ) 3
2
H
wp w w w w w w
wp w
÷ = ÷ = ÷ = + ÷
1/3
1/3
1 3 4 3 3 3 1 3 3
2 3
2 2 2
H i i i
wp
wp
 
÷ ÷ ÷ + + ÷ +
÷ = ÷ ÷ = =


\ .
Prepared by Mrityunjoy Dutta
(iii)
2 1/3 2 2 2
2 1/3 2
2
2 2 2( ) 3
2
H
w p w w w w w w
w p w
÷ = ÷ = ÷ = + ÷
2 1/3
2 1/3
1 3 4 3 3 3 1 3 3
2 3
2 2 2
H i i i
w p
w p
 
÷ + ÷ + ÷ ÷ ÷
÷ = ÷ ÷ = =


\ .
So, roots of equation (2) are
1 3 3 1 3 3
1, ,
2 2
i i
   
÷ + ÷ ÷
 
 
\ . \ .
.
Now, roots of given equation (1) are
2 1 3 3 2 1 3 3 2
1 , ,
3 2 3 2 3
i i ÷ + ÷ ÷
÷ ÷ ÷
1 3 9 3 4 3 9 3 4
, ,
3 6 6
i i ÷ + ÷ ÷ ÷ ÷
=
1 7 9 3 7 9 3
, ,
3 6 6
i i ÷ + ÷ ÷
= (Ans).
NovDec, 2009
29. Write the relation between roots and coefficients of the equation.
1 2
0 1 2 1
.......... 0
n n n
n n
a x ax a x a x a
÷ ÷
÷
+ + + + + =
Ans: Let
1 2
, ,.........,
n
are roots of
1 2
0 1 2 1
.......... 0
n n n
n n
a x ax a x a x a
÷ ÷
÷
+ + + + + = .
Then
1
1
0
i
i n
a
a
s s
= ÷
¿
,
2 2
0
( 1)
i j
i j
a
a
=
= ÷
¿
3 3
0
( 1)
i j k
i j k
a
a
= =
= ÷
¿
Similarly,
1 2
0
......... ( 1)
n n
n
a
a
= ÷
30. I f , , are the roots of the equation
3
0 x px q + + = , then show that
i.
5 5 5
5 + + = ÷
¿
ii.
2 5 3 4
3 5 =
¿ ¿ ¿ ¿
.
Ans: As , , are the roots of the cubic
3
0 x px q + + = .(1)
So, 0, , p q = = = ÷
¿ ¿
Now,
( )
2
2
2 0 2 2 p p = ÷ = ÷ = ÷
¿ ¿ ¿
.
2
2p ¬ = ÷
¿
(2)
As
3 3
0 3 0 3( ) 0 q = ¬ ÷ = ¬ ÷ ÷ =
¿ ¿ ¿
Prepared by Mrityunjoy Dutta
3
3q ¬ = ÷
¿
(3)
Let us multiply equation (1) by x we get
4 2
0 x px qx + + =
4 2
0 p q ¬ + + =
¿ ¿ ¿
4 2 2
( 2 ) (0) 2 p q p p q p ¬ = ÷ ÷ = ÷ ÷ ÷ =
¿ ¿ ¿
4 2
2p ¬ =
¿
(3)
(i)
5 5 5
5 + + = ÷
¿
Ans: Now by multiplying (1) by
2
x we get
5 3 2
0 x px qx + + =
5 3 2
0 p q + + =
¿ ¿ ¿
5 3 2
( 3 ) ( 2 ) 5 p q p q q p pq ¬ = ÷ ÷ = ÷ ÷ ÷ ÷ =
¿ ¿ ¿
(4)
5
5( ) q p ¬ = ÷ ÷
¿
5
5 ¬ = ÷
¿ ¿
5 5 5
5 ¬ + + = ÷
¿
(Proved)
(ii)
2 5 3 4
3 5 =
¿ ¿ ¿ ¿
Ans:
2 5 2
3 3.( 2 ).(5 ) 30 p pq p q = ÷ = ÷
¿ ¿
(5)
3 4 2 2
5 5( 3 )(2 ) 30 q p p q = ÷ = ÷
¿ ¿
(6)
From(5) and (6)
2 5 3 4
3 5 ¬ =
¿ ¿ ¿ ¿
(Proved)
31. Show that the equation
4 3 2
10 23 6 15 0 x x x x ÷ + ÷ ÷ = can be transformed into reciprocal
equation by diminishing the roots by 2. Hence solve the equation
Ans: Let us diminished the roots of
4 3 2
10 23 6 15 0 x x x x ÷ + ÷ ÷ = (1) by 2.
Putting 2 2 y x x y = ÷ ¬ = +
By Using synthetic division method
Prepared by Mrityunjoy Dutta
The transformed equation is
4 3 2
2 13 2 1 0 y y y y ÷ ÷ ÷ + = (2)
Equation (2) is a reciprocal equation of even degree having coefficients of terms
equidistant fromthe beginning and end equal.
Dividing equation (2) by
2
y we get
2
2
2 1
2 13 0 y y
y y
÷ ÷ ÷ + =
2
2
1 1
2 13 0 y y
y y
   
¬ + ÷ + ÷ =
 
\ . \ .
Now putting
2 2
2
1 1
2 y z y z
y y
+ = ¬ + = ÷
2
2 2 13 0 z z ¬ ÷ ÷ ÷ =
2
2 15 0 ( 5)( 3) 0 z z z z ¬ ÷ ÷ = ¬ ÷ + =
3,5 z ¬ = ÷
1
3 y
y
¬ + = ÷
1
5 y
y
¬ + =
2
1 3 y y ¬ + = ÷
2
1 5 y y ¬ + =
2
3 1 0 y y ¬ + + =
2
5 1 0 y y ¬ ÷ + =
3 9 4
2
y
÷ ± ÷
¬ =
5 25 4
2
y
± ÷
¬ =
Prepared by Mrityunjoy Dutta
3 5
2
y
÷ ±
¬ =
5 21
2
y
±
¬ =
3 5 3 5 5 21 5 21
, , ,
2 2 2 2
y
÷ + ÷ ÷ + ÷
¬ =
So, solution for 2 x y = +
3 5 3 5 5 21 5 21
2, 2, 2, 2
2 2 2 2
x
÷ + ÷ ÷ + ÷
¬ = + + + +
1 5 1 5 9 21 9 21
, , ,
2 2 2 2
x
+ ÷ + ÷
¬ = (Ans)
32. Solve by Cardan’s method, the equation
3 2
27 54 198 73 0 x x x + + ÷ = .
Ans:
3 2
27 54 198 73 0 x x x + + ÷ =
3 2
22 73
2 0
3 27
x x x ¬ + + ÷ = (1)
Let us compare this equation with
3 2
0 ax bx cx d + + + =
Then
22 73
1, 2, ,
3 27
a b c d ¬ = = = = ÷
Putting
2 2
3 3
z ax b x x z = + = + ¬ = ÷ in (1) we get
3 2
2 2 22 2 73
2 0
3 3 3 3 27
z z z
     
¬ ÷ + ÷ + ÷ ÷ =
  
\ . \ . \ .
3 2 2
4 8 8 8 22 44 73
2 2 0
3 27 3 9 3 9 27
z z z z z z ¬ ÷ + ÷ + ÷ + + ÷ ÷ =
3
6 7 0 z z ¬ + ÷ = (2)
Now comparing with
3
3 0 z Hz G + + =
Where 2, 7 H G = = ÷
 
3 2
1 1 1
4 7 32 49 7 9 8
2 2 2
p G H G
(
(
= ÷ + + = + + = + =
¸ ¸
¸ ¸
So roots of given cubic equation (2) are
(i)
1/3
1/3
2
2 1
2
H
p
p
÷ = ÷ =
(ii)
1/3 2 2 2
1/3
2
2 2 2( ) 3
2
H
wp w w w w w w
wp w
÷ = ÷ = ÷ = + ÷
1/3
1/3
1 3 4 3 3 3 1 3 3
2 3
2 2 2
H i i i
wp
wp
 
÷ ÷ ÷ + + ÷ +
÷ = ÷ ÷ = =


\ .
Prepared by Mrityunjoy Dutta
(iii)
2 1/3 2 2 2
2 1/3 2
2
2 2 2( ) 3
2
H
w p w w w w w w
w p w
÷ = ÷ = ÷ = + ÷
2 1/3
2 1/3
1 3 4 3 3 3 1 3 3
2 3
2 2 2
H i i i
w p
w p
 
÷ + ÷ + ÷ ÷ ÷
÷ = ÷ ÷ = =


\ .
So, roots of equation (2) are
1 3 3 1 3 3
1, ,
2 2
i i
   
÷ + ÷ ÷
 
 
\ . \ .
.
Now, roots of given equation (1) are
2 1 3 3 2 1 3 3 2
1 , ,
3 2 3 2 3
i i ÷ + ÷ ÷
÷ ÷ ÷
1 3 9 3 4 3 9 3 4
, ,
3 6 6
i i ÷ + ÷ ÷ ÷ ÷
=
1 7 9 3 7 9 3
, ,
3 6 6
i i ÷ + ÷ ÷
= (Ans).
MayJ une 2010
33. I f , , are the roots of the equation 0 8 12 6
2 3
= ÷ + ÷ x x x , find an equation whose
roots are 2 , 2 , 2 ÷ ÷ ÷ .
Ans:  It is same as to find an equation whose roots are diminished by 2 of
0 8 12 6
2 3
= ÷ + ÷ x x x 0 ) 2 (
3
= ÷ ¬ x (1) Let 2 2 + = ¬ ÷ = y x x y ,
so eqn (1) becomes 0
3
= ¬ y . Then the equation is
3
0 x = .
34. I f the roots of the equation 0
2 3
= ÷ + ÷ r qx px x are in H.P., then prove that
0 2 9 27
3 2
= + ÷ q pqr r .
Ans:  Let , , are the roots of the equation 0
2 3
= ÷ + ÷ r qx px x .
Here , , p q r + + = + + = =
Given that roots are in HP.
So,
1 1 2
+ =
2
2 3
+
¬ = ¬ + = ¬ + + =
( )
( )
3 3
3
r
q
¬ + + = ¬ = =
+ +
As is a root of the given eqn so it must satisfy the equation.
Hence
3 2
0 p q r ÷ + ÷ =
Prepared by Mrityunjoy Dutta
3 2
3 2 3
3
3 3 3 27 9 2
0 0
r r r r pqr rq
p q r
q q q q
      ÷ +
¬ ÷ + ÷ = ¬ =
  
\ . \ . \ .
3 2 3
27 9 2 0 r pqr rq ¬ ÷ + =
2 3
27 9 2 0 r pqr q ¬ ÷ + = (Proved).
35. I f , , are the roots of the equation 0
3
= + + r qx x , form an equation whose roots are:
(i)
, , .
(ii)
2 2 2
, ,
+ + +
Ans:  Here 0, , q r + + = + + = = ÷
i. , ,
Let
2
2 2 2 2 2 2 2
, , , , , ,
r r r r r
y x
x y
÷ ÷ ÷ ÷ ÷
= = = = ¬ =
Now, 0
3
= + + r qx x
3 6 4 2 2 2
2 x qx r x qx q x r ¬ + = ÷ ¬ + + =
3 2
2 2
2
r r r
q q r
y y y
    ÷ ÷ ÷
¬ + + =
 
\ . \ .
3 2
2 2
3 2
2
r r r
q q r
y y y
÷
¬ + ÷ =
2 2 2 3
2 r qry q y ry ¬ ÷ + ÷ =
3 2 2 2
2 0 ry q y qry r ¬ + ÷ + =
New eqn is
3 2 2 2
2 0 rx q x qrx r ¬ + ÷ + =
(ii)
2 2 2
, ,
+ + +
Ans:  Here 0, , q r + + = + + = = ÷
Let
2 2 2 2 2 2
1 1 1
, , , , y
+ + + + + + + + +
= = ÷ ÷ ÷
1
,
1
,
1 1
0 ,
1
0 ,
1
0 ÷ ÷ ÷ = ÷ ÷ ÷ = ¬ y as 0 + + =
y
x
x
y
1 1
÷ = ¬ ÷ = ¬
Prepared by Mrityunjoy Dutta
So, eqn 0
3
= + + r qx x becomes 0 1 0
1 1
3 2
3
= + ÷ ÷ ¬ = +


.

\

÷ +


.

\

÷ ry qy r
y
q
y
0 1
2 3
= ÷ ÷ ¬ qy ry
New eqn is 0 1
2 3
= ÷ ÷ ¬ qx rx
36. Solve by Cardan’s method: 0 1 9 28
2 3
= + ÷ x x
Ans:  0 1 9 28
2 3
= + ÷ x x (1)
Let
1 1
y x
x y
= ¬ = , then eqn (1) becomes
3
9 28 0 y y ÷ + = (2)
Here the equation having terms involving
2
y termmissing.
Let y u v = + be the solution of equation (2).
3 3 3
3 ( ) y u v uv u v ¬ = + + +
3 3 3
3 y u v uvy ¬ = + +
( )
3 3 3
3 0 y uvy u v ¬ ÷ ÷ + = (3)
By comparing equation(2) and (3) we get
3 3
3, 28 uv u v ¬ = + = ÷
3 3 3 3
27, 28 u v u v ¬ = + = ÷
So,
3 3
, u v are the roots of the equation
2
28 27 0 t t + + =
( 1)( 27) 0 1, 27 t t t ¬ + + = ¬ = ÷ ÷ . So, let
3 3
1, 27 u v = ÷ = ÷ .
2
1, , u w w ¬ = ÷ ÷ ÷ , then
2
3
3, 3 , 3 v w w
u
¬ = = ÷ ÷ ÷
Then
2 2
1 3, 3 , 3 y u v w w w w ¬ = + = ÷ ÷ ÷ ÷ ÷ ÷
2
4,1 2 ,1 2 y u v w w ¬ = + = ÷ ÷ ÷
1 3 1 3
4,1 2 ,1 2
2 2
i i
y u v
   
÷ ÷ ÷ +
¬ = + = ÷ ÷ ÷
 
 
\ . \ .
4,2 3,2 3 y i i ¬ = ÷ + ÷
1 1 2 3 2 3
, ,
4 7 7
i i
x
y
÷ ÷ +
¬ = =
So, roots are
1 2 3 2 3
, ,
4 7 7
i i
x
÷ ÷ +
= . (Ans).
NovDec 2010
Prepared by Mrityunjoy Dutta
37. State the intermediate property.
Ans Intermediate property of roots says that for the equation ( ) 0 f x = for two numbers
let a and b such that, ) (a f and ) (b f have different sign then equation 0 ) ( = x f has at least
one root lies between a and b.
38. I f , , are the roots of the equation
3
0 x px q + + = , then show that
i.
5 5 5
5 + + = ÷
¿
ii.
2 5 3 4
3 5 =
¿ ¿ ¿ ¿
.
Ans: As , , are the roots of the cubic
3
0 x px q + + = .(1)
So, 0, , p q = = = ÷
¿ ¿
Now,
( )
2
2
2 0 2 2 p p = ÷ = ÷ = ÷
¿ ¿ ¿
.
2
2p ¬ = ÷
¿
(2)
As
3 3
0 3 0 3( ) 0 q = ¬ ÷ = ¬ ÷ ÷ =
¿ ¿ ¿
3
3q ¬ = ÷
¿
(3)
Let us multiply equation (1) by x we get
4 2
0 x px qx + + =
4 2
0 p q ¬ + + =
¿ ¿ ¿
4 2 2
( 2 ) (0) 2 p q p p q p ¬ = ÷ ÷ = ÷ ÷ ÷ =
¿ ¿ ¿
4 2
2p ¬ =
¿
(3)
(i)
5 5 5
5 + + = ÷
¿
Ans: Now by multiplying (1) by
2
x we get
5 3 2
0 x px qx + + =
5 3 2
0 p q + + =
¿ ¿ ¿
5 3 2
( 3 ) ( 2 ) 5 p q p q q p pq ¬ = ÷ ÷ = ÷ ÷ ÷ ÷ =
¿ ¿ ¿
(4)
5
5( ) q p ¬ = ÷ ÷
¿
5
5 ¬ = ÷
¿ ¿
5 5 5
5 ¬ + + = ÷
¿
(Proved)
(ii)
2 5 3 4
3 5 =
¿ ¿ ¿ ¿
Ans:
2 5 2
3 3.( 2 ).(5 ) 30 p pq p q = ÷ = ÷
¿ ¿
(5)
3 4 2 2
5 5( 3 )(2 ) 30 q p p q = ÷ = ÷
¿ ¿
(6)
From(5) and (6)
2 5 3 4
3 5 ¬ =
¿ ¿ ¿ ¿
(Proved)
Prepared by Mrityunjoy Dutta
39. Solve:
5 4 3 2
6 41 97 97 41 6 0 x x x x x ÷ + ÷ + ÷ = .
Ans:
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + =
The given equation is a reciprocal equation of odd degree having coefficient of terms
equidistance frombeginning and end.
So, 1 x= ÷ is its root.
4 3 2
( 1)(6 5 38 5 6) 0 x x x x x ¬ + ÷ ÷ ÷ + =
4 3 2
(6 5 38 5 6) 0 x x x x ¬ ÷ ÷ ÷ + =
Dividing by
2
x we get
2
2
5 6
6 5 38 0 x x
x x
¬ ÷ ÷ ÷ + =
2
2
1 1
6 5 38 0 x x
x x
   
¬ + ÷ + ÷ =
 
\ . \ .
2
1 1
6 2 5 38 0 x x
x x
 
   
¬ + ÷ ÷ + ÷ =

 

\ . \ .
\ .
( )
2
6 2 5 38 0 t t ¬ ÷ ÷ ÷ = where
1
x t
x
 
+ =

\ .
2
6 5 50 0 t t ¬ ÷ ÷ =
10 5
(3 10)(2 5) 0 ,
3 2
t t t ¬ ÷ + = ¬ = ÷
1 10 1 5
3 2
x and x
x x
¬ + = ¬ + = ÷
2 2
3 3 10 2 2 5 x x and x x ¬ + = ¬ + = ÷
2 2
3 10 3 0 2 5 2 0 x x and x x ¬ ÷ + = ¬ + + =
10 100 36 5 25 16
6 4
x and x
± ÷ ÷ ± ÷
¬ = ¬ =
10 8 5 3
6 4
x and x
± ÷ ±
¬ = ¬ =
1 1
3, 2,
2 2
x and x ¬ = ¬ = ÷ ÷
So, roots are
1 1
2, 1, , , 3
2 2
x ¬ = ÷ ÷ ÷ (Ans)
40. Solve by Ferrari’s method: 0 3 10 5 2
2 3 4
= ÷ + ÷ ÷ x x x x .
Prepared by Mrityunjoy Dutta
Ans:  0 3 10 5 2
2 3 4
= ÷ + ÷ ÷ x x x x
(1)
Equation (1) can be written as by combining
x
4
and x
3
into perefect square
0 ) ( ) (
2 2 2
= + ÷ + ÷ n mx x x (2)
0 ) 2 2 ( ) 1 2 ( 2
2 2 2 2 3 4
= ÷ + ÷ ÷ + ÷ + + ÷ ¬ n mn x m x x x (3)
From (1)onJ (3)
¸
+ = ¬ ÷ = ÷
÷ ÷ = ¬ = ÷ ÷
+ = ¬ ÷ = ÷ +
¬
3 3
5 10 2 2
6 2 5 1 2
2 2 2 2
2 2
n n
mn mn
m m
(4)
From(4)
2 2 2
) ( . mn n m = ¬
2 2
) 5 ( ) 3 ).( 6 2 ( ÷ ÷ = + + ¬
0 7 4 5 2
2 3
= ÷ ÷ + ¬
Then 1 ÷ = ¬ is one of the root.
So, 2 4 6 ) 1 ( 2
2
= ¬ = + ÷ = ¬ m m (one of the value)
2 4 5 ÷ = ¬ ÷ = ÷ ÷ = ¬ n mn
So, (2) can be written as 0 ) 2 2 ( ) 1 (
2 2 2
= ÷ ÷ ÷ ÷ x x x
0 ) 2 2 1 )( 2 2 1 (
2 2
= + ÷ ÷ ÷ ÷ + ÷ ÷ ¬ x x x x x x
0 ) 1 3 )( 3 (
2 2
= + ÷ ÷ + ¬ x x x x
0 ) 1 3 ( , 0 ) 3 (
2 2
= + ÷ = ÷ + ¬ x x x x
2
4 9 3
,
2
12 1 1 ÷ ±
=
+ ± ÷
= ¬ x x
2
5 3
,
2
13 1 ±
=
± ÷
= ¬ x x (Ans)
April May2011
41. What is geometrical meaning of root of the equation f(x)=0
Ans. For any value of x which satisfies 0 ) ( = x f are called as solution of 0 ) ( = x f or root of
0 ) ( = x f .
Example:  For 0 6 2 = + x
a. If 2 = x , it is not satisfies 0 6 2 = + x . So, 2 = x is not a solution of 0 6 2 = + x .
If 3 ÷ = x , it is not satisfies 0 6 2 = + x . So, 3 ÷ = x is a solution of 0 6 2 = + x .
Geometrically for the curve f(x) =0 the roots are the curve of , , ,................ x a x b x c = = =
which touches the curve at a, b, and c respectively.
Prepared by Mrityunjoy Dutta
42. Solve the following equations : 6x
5
41x
4
+97x
3
97x
2
+41x6=0
Ans:
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + =
The given equation is a reciprocal equation of odd degree having coefficient of terms
equidistance frombeginning and end.
So, 1 x= ÷ is its root.
4 3 2
( 1)(6 5 38 5 6) 0 x x x x x ¬ + ÷ ÷ ÷ + =
4 3 2
(6 5 38 5 6) 0 x x x x ¬ ÷ ÷ ÷ + =
Dividing by
2
x we get
2
2
5 6
6 5 38 0 x x
x x
¬ ÷ ÷ ÷ + =
2
2
1 1
6 5 38 0 x x
x x
   
¬ + ÷ + ÷ =
 
\ . \ .
2
1 1
6 2 5 38 0 x x
x x
 
   
¬ + ÷ ÷ + ÷ =

 

\ . \ .
\ .
( )
2
6 2 5 38 0 t t ¬ ÷ ÷ ÷ = where
1
x t
x
 
+ =

\ .
2
6 5 50 0 t t ¬ ÷ ÷ =
10 5
(3 10)(2 5) 0 ,
3 2
t t t ¬ ÷ + = ¬ = ÷
1 10 1 5
3 2
x and x
x x
¬ + = ¬ + = ÷
2 2
3 3 10 2 2 5 x x and x x ¬ + = ¬ + = ÷
2 2
3 10 3 0 2 5 2 0 x x and x x ¬ ÷ + = ¬ + + =
10 100 36 5 25 16
6 4
x and x
± ÷ ÷ ± ÷
¬ = ¬ =
10 8 5 3
6 4
x and x
± ÷ ±
¬ = ¬ =
1 1
3, 2,
2 2
x and x ¬ = ¬ = ÷ ÷
So, roots are
1 1
2, 1, , , 3
2 2
x ¬ = ÷ ÷ ÷ (Ans)
Prepared by Mrityunjoy Dutta
43. Find the equation of squared difference of the roots of the cubic
3 2
x 6x 7x 2 0. + + + =
Ans: Let , , are the roots of
3 2
x 6x 7x 2 0. + + + = …………………(1)
Now, 6 + + = ÷ (2)
7 + + = (3)
2 = ÷ (4)
As sum of the roots is 6 therefore to remove the 2
nd
term we will make a new equation
whose roots will be increased by 2
Here by removing the term containing
2
x
We will have
2 1 6 7 2
0 2 8 2
1 4 1 4
0 2 4
1 2 5
0 2
1 0
÷
÷ ÷
÷
÷ ÷
÷
÷
The transformed equation will be
3
5y 4 0. y + = and roots of it will be 2, 2, 2 + + + …(5)
Let 2, 2, 2 a b c = + = + = +
Now, 0 a b c + + = (6)
5 ab bc ca + + = ÷ (7)
4 abc = ÷ (8)
( ) ( )
( ) ( )
( ) ( )
2 2
2 2
2 2
b c
c a
a b
÷ = + ÷ + = ÷
÷ = + ÷ + = ÷
÷ = + ÷ + = ÷
And we are here to find
( ) ( ) ( )
2 2 2
, , ÷ ÷ ÷
which is equivalent to
( ) ( ) ( )
2 2 2
, , a b b c c a ÷ ÷ ÷ if z be the root of the equation squared differences we will have
( ) ( )
2 2
4 z b c b c bc = ÷ = + ÷
( ) ( )
2 2
4 z b c b c bc ¬ = ÷ = + ÷ from equation 6 and 8 we will have
( ) ( ) ( )
3
2 2 2 4 16
4
abc a
z b c b c bc a
a a
+
¬ = ÷ = + ÷ ¬ ÷ ÷ =
Prepared by Mrityunjoy Dutta
3
16 a
z
a
+
¬ =
3
16 y
z
y
+
¬ = as y is the root of the equation
3
5y 4 0. y + = and equivalent to a, b, and c
3
16 0 y zy ¬ ÷ + = ………………………(9)
Subtracting the equation 9 from equation 8 we will have ( )
( )
12
5 12 0
5
z y y
z
¬ ÷ ÷ = ¬ =
÷
Putting the value of y in the equation 8 we will have
( ) ( )
3
12 12
5 4 0.
5 5 z z
   
+ =
 
 
÷ ÷
\ . \ .
3 2
30z 225 68 0. z z + ÷ = and roots of the obtained equation are ( ) ( ) ( )
2 2 2
, , a b b c c a ÷ ÷ ÷
which is equivalent to ( ) ( ) ( )
2 2 2
, , ÷ ÷ ÷ .
Hence
3 2
30z 225 68 0. z z + ÷ = is the required equation.
44. Solve by Cardan’s methods: x
3
3x+1=0.
Ans:
3
3 1 0 x x ÷ + = (1)
Hence the transformed equation is
3
3 1 0 x x ÷ + = (2)where
Let
1/3 1/3
x p q = + be the solution of equation (2).
( )
3 1/3 1/3 1/3 1/3
3 x p q p q p q ¬ = + + +
3 1/3 1/3
3 x p q p q x ¬ = + +
3 1/3 1/3
3 ( ) 0 y p q y p q ¬ ÷ ÷ + = (3)
By comparing equation (2) and (3) we get
1/3 1/3
1, ( ) 1 p q p q ¬ = + =
1, ( ) 1 pq p q ¬ = + =
So, p and q are the roots of the equation
2
1 0 t t + + =
1 1 4 1 3
2 2
i
t
÷ ± ÷ ÷ ±
¬ = = .
Prepared by Mrityunjoy Dutta
So, let
1 3 1 3
,
2 2
i i
p q
÷ + ÷ ÷
= = .
So roots of given cubic equation (1) are
(i)
1/3 1/3
1/3 1/3
1 3 1 3
2 2
i i
p q
   
÷ + ÷ ÷
+ = +
 
 
\ . \ .
1/3 1/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
2 2 2 2
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
2
2cos
9
=
(ii)
1/3 1/3
1/3 2 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
wp wq
     
÷ + ÷ + ÷ ÷ ÷ ÷
+ = +
   
   
\ .\ . \ .\ .
4/3 4/3
1 3 1 3
2 2
i i
   
÷ + ÷ ÷
= +
 
 
\ . \ .
4/3 4/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
8 8 8 8
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
8
2cos
9
=
(iii)
1/3 1/3
2 1/3 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
w p wq
      
÷ ÷ ÷ + ÷ + ÷ ÷
+ = +
   
   
\ .\ . \ . \ .
1/3 1/3
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 3 3 3 3 3 3
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 9 9 3 3 9 9
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
Prepared by Mrityunjoy Dutta
2 2 2 2 2 2 2 2
cos sin cos sin
9 3 9 3 9 3 9 3
i i
           
= ÷ + ÷ + ÷ ÷ ÷
     
\ . \ . \ . \ . \ . \ .
4 4 4 4
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
4 4 14
2cos 2cos 2 2cos
9 9 9
 
= = ÷ =

\ .
So, roots of equation (2) are
2 8 14
2cos , 2cos , 2cos
9 9 9
DecJ an2011
45. Explain Descartes’ rule of sign of equation.
Ans Descarte’s Rule of Sign:
a. Maximum number of positive real root of 0 ) ( = x f is same as the number of sign changes
in ) (x f .
b. Maximum number of negative real root of 0 ) ( = x f is same as the number of sign changes
in ) ( x f ÷ .
c. If an equation having degree n such that at most p number of positive roots, at most q
number of negative roots, then equation has atleast ) ( q p n + ÷ number of imaginary
roots.
46. I f O, A, B, C are the four point on a straight line such that the distance of A, B and C from
O are the roots of the equation
3
3 0 ax cx d + + = . If B is the middle point of AC show that
3 3
3 2 0 a d abc b ÷ + =
Ans . Let us assume , , are the roots of the equation
3 2
3 3 0 ax bx cx d + + + = and
, , OA OB OC = = =
According to the given condition ÷ = ÷
2 = + (1)
According to the property of roots
Now,
3b
a
÷
+ + = (2)
Prepared by Mrityunjoy Dutta
3c
a
+ + = (3)
d
a
÷
= (4)
From 2 and 3 we will have
3
3
b b
a a
÷
= ÷ ¬ = (5)
( )
3 3 c c
a a
+ + = ¬ + + =
From 1
2
2
3 3
2 2
c b c
a a a
÷  
+ = ¬ + =

\ .
2
2
3
2
c b
a a
¬ = ÷ (6)
again from 4 we have
d
a
÷
=
( )
d
a
÷
=
From 5 and 6 we have
2
2
3
2
b c b d
a a a a
  ÷ ÷  
÷ =
 
\ .
\ .
By solving above we will have
( )
2
2
3 2 ca b
b d
a
  ÷
=

\ .
Hence we will have
3 3
3 2 0 a d abc b ÷ + =
47. Solve by Cardan’s methods : X
3
– 3X
2
+3 =0.
Ans:
3 2
3 3 0 x x ÷ + = (1)
Here we can remove second termof equation (1) by diminishing its roots by
3
1
3 1
b
h
na
÷
= ÷ = ÷ =
×
We can diminished each root by 1 by synthetic division method
Prepared by Mrityunjoy Dutta
Hence the transformed equation is
3
3 1 0 y y ÷ + = (2)where 1 y x = ÷
Let
1/3 1/3
y p q = + be the solution of equation (2).
( )
3 1/3 1/3 1/3 1/3
3 y p q p q p q ¬ = + + +
3 1/3 1/3
3 y p q p q y ¬ = + +
3 1/3 1/3
3 ( ) 0 y p q y p q ¬ ÷ ÷ + = (3)
By comparing equation (2) and (3) we get
1/3 1/3
1, ( ) 1 p q p q ¬ = + =
1, ( ) 1 pq p q ¬ = + =
So, p and q are the roots of the equation
2
1 0 t t + + =
1 1 4 1 3
2 2
i
t
÷ ± ÷ ÷ ±
¬ = = .
So, let
1 3 1 3
,
2 2
i i
p q
÷ + ÷ ÷
= = .
So roots of given cubic equation (1) are
(i)
1/3 1/3
1/3 1/3
1 3 1 3
2 2
i i
p q
   
÷ + ÷ ÷
+ = +
 
 
\ . \ .
1/3 1/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
Prepared by Mrityunjoy Dutta
2 2 2 2
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
2
2cos
9
=
(ii)
1/3 1/3
1/3 2 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
wp wq
     
÷ + ÷ + ÷ ÷ ÷ ÷
+ = +
   
   
\ .\ . \ .\ .
4/3 4/3
1 3 1 3
2 2
i i
   
÷ + ÷ ÷
= +
 
 
\ . \ .
4/3 4/3
2 2 2 2
cos sin cos sin
3 3 3 3
i i
   
= + + ÷
 
\ . \ .
8 8 8 8
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
8
2cos
9
=
(iii)
1/3 1/3
2 1/3 1/3
1 3 1 3 1 3 1 3
2 2 2 2
i i i i
w p wq
      
÷ ÷ ÷ + ÷ + ÷ ÷
+ = +
   
   
\ .\ . \ . \ .
1/3 1/3
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 3 3 3 3 3 3
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin cos sin cos sin
3 3 9 9 3 3 9 9
i i i i
     
= ÷ + + + ÷
   
\ .\ . \ .\ .
2 2 2 2 2 2 2 2
cos sin cos sin
9 3 9 3 9 3 9 3
i i
           
= ÷ + ÷ + ÷ ÷ ÷
     
\ . \ . \ . \ . \ . \ .
4 4 4 4
cos sin cos sin
9 9 9 9
i i
   
= + + ÷
 
\ . \ .
4 4 14
2cos 2cos 2 2cos
9 9 9
 
= = ÷ =

\ .
So, roots of equation (2) are
2 8 14
2cos , 2cos , 2cos
9 9 9
Now, roots of given equation (1) are
2 8 14
1 2cos , 1 2cos , 1 2cos
9 9 9
+ + + (Ans)
Prepared by Mrityunjoy Dutta
48. Solve by Ferrari’s method:
4 3 2
12 41 18 72 0 x x x x ÷ ÷ ÷ ÷ = .
Ans:
4 3 2
12 41 18 72 0 x x x x ÷ + ÷ ÷ =
Let
4 3 2 2 2 2
( ) 12 41 18 72 ( 6 ) ( ) 0 f x x x x x x x mx n = ÷ + ÷ ÷ = ÷ + ÷ + = (1)
4 3 2 4 2 2 3 2 2 2 2
12 41 18 72 36 12 12 2 2 x x x x x x x x x mx mnx n ¬ ÷ + ÷ ÷ = + + ÷ ÷ + ÷ ÷ ÷
4 3 2 4 3 2 2 2 2
12 41 18 72 12 (36 2 ) ( 12 2 ) x x x x x x m x mn x n ¬ ÷ + ÷ ÷ = ÷ + + ÷ + ÷ ÷ + ÷
Equating the coefficients we get
2 2 2
(36 2 ) 41, ( 12 2 ) 18, 72 m mn n ¬ + ÷ = ÷ ÷ = ÷ ÷ = ÷
2 2 2
2 5, 9 6 , 72 m mn n ¬ = ÷ = ÷ = +
( )( ) ( )
2
2
2 5 72 9 6 ¬ ÷ + = ÷
3 2 2
2 144 5 360 81 36 108 0 ¬ + ÷ ÷ ÷ ÷ + =
3 2
2 41 252 441 0 ¬ ÷ + ÷ =
2
( 3)(2 35 147) 0 ¬ ÷ ÷ + =
21
2
3,7, ¬ =
By taking 3 1, 9 m n = ¬ = = ÷ equation (1) becomes
4 3 2 2 2 2
12 41 18 72 ( 6 3) ( 9) 0 x x x x x x x ¬ ÷ + ÷ ÷ = ÷ + ÷ ÷ =
2 2
( 6 3 9)( 6 3 9) 0 x x x x x x ¬ ÷ + + ÷ ÷ + ÷ + =
2 2
( 5 6)( 7 12) 0 x x x x ¬ ÷ ÷ ÷ + =
( 6)( 1)( 3)( 4) 0 x x x x ¬ ÷ + ÷ ÷ =
1,3,4,6 x ¬ = ÷ (Ans)
April May2012
49. Solve the equation
3
6x 20 0 x + + = , one root being 1 3. i ÷
Ans . As we know that from the general properties of roots of an equation that In an equation
with real coefficients, if i + is a root then i ÷ is also one of the root, therefore two
roots of the equation
3
( ) 6x 20 f x x = + + are 1 3. i ÷ and 1 3. i +
( ) ( )   ( ) 13i 1+3i f x x x x a ¬ = ÷ ÷ ÷ ( (
¸ ¸ ¸ ¸
( ) ( )   ( ) 1 3 1 3 f x x i x i x a ¬ = ÷ + ÷ ÷ ÷ ( (
¸ ¸ ¸ ¸
( ) ( )   ( ) 1 3 1 3 f x x i x i x a ¬ = ÷ + ÷ ÷ ÷ ( (
¸ ¸ ¸ ¸
Prepared by Mrityunjoy Dutta
( )  
2
( ) 1 9 f x x x a
(
¬ = ÷ ÷ ÷
¸ ¸
 
2
( ) 2 1 9 f x x x x a ( ¬ = ÷ + ÷ ÷
¸ ¸
 
2
( ) 2 8 f x x x x a ( ¬ = ÷ ÷ ÷
¸ ¸
 
2
( )
2 8
f x
x a
x x
¬ = ÷
( ÷ ÷
¸ ¸
 
3
2
6x 20
2 8
x
x a
x x
( + +
¸ ¸
¬ = ÷
( ÷ ÷
¸ ¸
    2 2 x x a a ¬ + = ÷ ¬ = ÷
Roots of the equation
3
6x 20 x ( + +
¸ ¸
are 1 3.,1 3 2 i i and ÷ + ÷ and
50. Solve the equation Solve the equation
3 2
x 4x 20x 48 0 ÷ ÷ + = , given that the roots o onJ [
are connected by the relation 0 + =
Ans . Let us assume , , are the roots of the equation
3 2
x 4x 20x 48 0 ÷ ÷ + = and
According to the given condition 0 + = ¬ = ÷ (1)
According to the property of roots
Now, 4 + + = (2)
From 1 we will have 0 4 4 + = ¬ =
20 + + = ÷ (3)
48 = ÷ (4)
From 2 and 4 we will have ( ) 4 48 12 = ÷ ¬ = ÷ (5)
By using the equation 1 and 5 we 0 + = and 12 = ÷
We can have quadratic equation from above i.e
2
12 0 y = and 2 3 y= ±
2 3 2 3 and = = ÷ and three roots of the equation
3 2
x 4x 20x 48 0 ÷ ÷ + = are
2 3 , 2 3 4 and = = ÷ =
51. Solve the equation
3 2
6x 11x 3x 2 0 ÷ ÷ + = , given that its roots are in H.P.
Ans. We know that H.P is reciprocal of A.P then by taking 1/ y x = the new equation will be
3 2
3 2
1 1 1
6 11 3 2 0 2 3y 11 6 0 y y
y y y
     
÷ ÷ + = ¬ ÷ ÷ + =
  
\ . \ . \ .
now roots of the equation
3 2
2 3y 11 6 0 y y ÷ ÷ + = are in A.P As , , d d ÷ + are the roots of the cubic equation
3 2
2 3y 11 6 0 y y ÷ ÷ + = .
Prepared by Mrityunjoy Dutta
By properties of relation between roots and coefficient of the equation we will have
( ) ( ) ( ) 3/ 2 d d ¬ ÷ + + + =
3 3/ 2 1/ 2 ¬ = ¬ =
Again we will have ( ) ( ) ( ) 3 d d ¬ ÷ × × + = ÷
( ) ( )
2 2
3 d ¬ ÷ × = ÷
2
2
1 1
3
2 2
d
 
   
¬ ÷ × = ÷

 

\ . \ .
\ .
2
1
6
4
d
   
¬ ÷ = ÷
 
\ . \ .
2
1 25
6
4 4
d
 
¬ = + =

\ .
5
2
d ¬ = ± by putting the value of 5/ 2 d = in , , d d ÷ + we will have roots of the
equation
3 2
2 3y 11 6 0 y y ÷ ÷ + = are 2,1/ 2,3 ÷ and roots of the equation
3 2
6x 11x 3x 2 0 ÷ ÷ + = are 1/ 2, 2 1/ 3 and ÷
52. Solve by Cardan’s methods:
3
x 18x 35 0. ÷ + =
Ans:
3
x 18x 35 0. ÷ + =
Here the equation having terms involving
2
x termmissing.
Let x u v = + be the solution of equation (1).
( )
3 3 3
3 x u v uv u v ¬ = + + +
3 3 3
3 x u v uvx ¬ = + +
( )
3 3 3
3 0 x uvx u v ¬ ÷ ÷ + = (2)
By comparing equation(1) and (2) we get
3 3
6, ( ) 35 uv u v ¬ = + = ÷ (3)
3 3 3 3 3 3
6, ( ) 35 216, ( ) 35 uv u v u v u v ¬ = + = ÷ ¬ = + = ÷
So,
3
u and
3
v are the roots of the equation
2
35 216 0 t t + + =
2
35 216 ( 27)( 8) 27, 8 t t t t t ¬ + + = + + ¬ = ÷ ÷ .
So, let
3
u =27 and
2
3, 3 , 3 u w w = ÷ ÷ ÷ therefore from3 we will have
2
2, 2 , 2 v w w = ÷ ÷ ÷
So roots of given cubic equation (1) are
(iv) 3 2 5 u v + = ÷ ÷ = ÷
Prepared by Mrityunjoy Dutta
(v)
2
1 3 1 3 5 3
3 2 3 2
2 2 2
i i i
u v w w
     
÷ + ÷ ÷ ÷
+ = ÷ ÷ = ÷ ÷ =
  
  
\ . \ . \ .
(vi)
2
1 3 1 3 5 3
3 2 3 2
2 2 2
i i i
u v w w
     
÷ ÷ ÷ + +
+ = ÷ ÷ = ÷ ÷ =
  
  
\ . \ . \ .
So, roots are
5 3 5 3
5, ,
2 2
i i
   
÷ +
÷
 
 
\ . \ .
(Ans).
Dec –J an 2012
53. From the equation of the fourth degree whose roots are 3 +i and √7 .
Ans . As we know that from the general properties of roots of an equation that In an equation
with real coefficients, if i + is a root then i ÷ is also one of the root, and for the
irrational roots if an equation has b a+ is one of the root, then b a÷ is also another root.
Therefore two roots of the equation we will have 3 i and 3i , 7 7 and + ÷ and the
equation will be
( ) ( )
( ) ( )
( ) 3+i 3i 7 7 f x x x x x
( (
= ÷ ÷ ÷ ÷ ÷ ( (
¸ ¸ ¸ ¸
¸ ¸ ¸ ¸
( ) ( ) ( ) 3 3 7 7 f x x i x i x x
( (
¬ = ÷ ÷ ÷ + ÷ + ( (
¸ ¸ ¸ ¸
¸ ¸ ¸ ¸
( )
( )
2
2
2 2
( ) 3 7 f x x i x
(
(
¬ = ÷ ÷ ÷
( ¸ ¸
¸ ¸
( )
( )
2
2
2 2
( ) 3 7 f x x i x
(
(
¬ = ÷ ÷ ÷
( ¸ ¸
¸ ¸
2 2
( ) 9 6 1 7 f x x x x ( ( ¬ = + ÷ + ÷
¸ ¸ ¸ ¸
4 2 2 3 2
( ) 7 9 63 6 42 7 f x x x x x x x ¬ = ÷ + ÷ ÷ + + ÷
4 3 2
( ) 6 3 42 70 f x x x x x ¬ = ÷ + + ÷
54. Solve the equations:
5 4 3 2
6x x 43x – 43x 6 0 . x + ÷ + + =
Ans:
5 4 3 2
6 43 43 6 0 x x x x x + ÷ ÷ + + =
The given equation is a reciprocal equation of odd degree having coefficient of terms
equidistance frombeginning and end.So, 1 x= ÷ is its root.
4 3 2
( 1)(6 5 38 5 6) 0 x x x x x ¬ + ÷ ÷ ÷ + =
4 3 2
(6 5 38 5 6) 0 x x x x ¬ ÷ ÷ ÷ + =
Dividing by
2
x we get
Prepared by Mrityunjoy Dutta
2
2
5 6
6 5 38 0 x x
x x
¬ ÷ ÷ ÷ + =
2
2
1 1
6 5 38 0 x x
x x
   
¬ + ÷ + ÷ =
 
\ . \ .
2
1 1
6 2 5 38 0 x x
x x
 
   
¬ + ÷ ÷ + ÷ =

 

\ . \ .
\ .
( )
2
6 2 5 38 0 t t ¬ ÷ ÷ ÷ = where
1
x t
x
 
+ =

\ .
2
6 5 50 0 t t ¬ ÷ ÷ =
10 5
(3 10)(2 5) 0 ,
3 2
t t t ¬ ÷ + = ¬ = ÷
1 10 1 5
3 2
x and x
x x
¬ + = ¬ + = ÷
2 2
3 3 10 2 2 5 x x and x x ¬ + = ¬ + = ÷
2 2
3 10 3 0 2 5 2 0 x x and x x ¬ ÷ + = ¬ + + =
10 100 36 5 25 16
6 4
x and x
± ÷ ÷ ± ÷
¬ = ¬ =
10 8 5 3
6 4
x and x
± ÷ ±
¬ = ¬ =
1 1
3, 2,
2 2
x and x ¬ = ¬ = ÷ ÷
So, roots are
1 1
2, 1, , , 3
2 2
x ¬ = ÷ ÷ ÷ (Ans)
55.
Solve by Cardan’s methods :
3
– 27x 54=0 x +
Ans:
3
– 27x 54=0 x +
Here the equation having terms involving
2
x termmissing.
Let x u v = + be the solution of equation (1).
( )
3 3 3
3 x u v uv u v ¬ = + + +
3 3 3
3 x u v uvx ¬ = + +
( )
3 3 3
3 0 x uvx u v ¬ ÷ ÷ + = (2)
By comparing equation(1) and (2) we get
Prepared by Mrityunjoy Dutta
3 3
9, ( ) 54 uv u v ¬ = + = ÷ (3)
3 3 3 3 3 3
9, ( ) 54 729, ( ) 54 uv u v u v u v ¬ = + = ÷ ¬ = + = ÷
So,
3
u and
3
v are the roots of the equation
2
54 729 0 t t + + =
2 2 2
54 27 ( 27) 27 t t t t ¬ + + = + ¬ = ÷ .
So, let
3
u =27 and
2
3, 3 , 3 u w w = ÷ ÷ ÷ therefore from3 we will have
2
3, 3 , 3 v w w = ÷ ÷ ÷
So roots of given cubic equation (1) are
(i) 3 3 6 u v + = ÷ ÷ = ÷
(ii)
2
1 3 1 3 6
3 3 3 3 3
2 2 2
i i
u v w w
   
÷ + ÷ ÷  
+ = ÷ ÷ = ÷ ÷ = =
 

 
\ .
\ . \ .
(iii)
2
1 3 1 3 6
3 3 3 3 3
2 2 2
i i
u v w w
   
÷ ÷ ÷ +  
+ = ÷ ÷ = ÷ ÷ = =
 

 
\ .
\ . \ .
So, roots are 6, 3, 3 ÷ (Ans).
56. Solve by Ferrari;s method : X
4
– 4X
3
–X
2
+16X – 12=0.
Ans:
4 3 2
– 4x – 16x – 12 0. x x + =
Let
4 3 2 2 2 2
( ) – 4x – 16x – 12 ( 2 ) ( ) 0 f x x x x x mx n = + = ÷ + ÷ + = (1)
4 3 2 4 2 2 3 2 2 2 2
– 4x – 16x – 12 4 4 4 2 2 x x x x x x x mx mnx n ¬ + = + + ÷ ÷ + ÷ ÷ ÷
4 3 2 4 3 2 2 2 2
– 4x – 16x – 12 4 (4 2 ) ( 4 2 ) x x x x m x mn x n ¬ + = ÷ + + ÷ + ÷ ÷ + ÷
Equating the coefficients we get
2 2 2
(4 2 ) 1, ( 4 2 ) 16, 12 m mn n ¬ + ÷ = ÷ ÷ ÷ = ÷ = ÷
2 2 2
2 5, 8 2 , 12 m mn n ¬ = + = ÷ ÷ = + ……………………..(2)
( )( ) ( )
2
2
2 5 12 8 2 ¬ + + = ÷ ÷
3 2 2
2 24 5 60 64 4 32 ¬ + + + = + +
3 2
2 8 4 0 ¬ + ÷ ÷ =
By solving the above equation we will have
2, 2, 1/ 2 ¬ = ÷ ÷
By taking 2, = in the equation 2 we will have
2 2
9, 12, 16 m mn n ¬ = = ÷ =
2
3, 12, 4 m mn n ¬ = ± = ÷ = ±
( ) ( )
3, 4 3, 4 m n or m n ¬ = = ÷ = ÷ =
Prepared by Mrityunjoy Dutta
By putting the value of above in the equation 1 we will have
4 3 2 2 2 2
( ) – 4x – 16x – 12 ( 2 2) (3 4) 0 f x x x x x x = + = ÷ + ÷ ÷ =
4 3 2 2 2
( ) – 4x – 16x – 12 ( 2 2) (3 4) ( 2 2) (3 4) f x x x x x x x x x ( ( = + = ÷ + ÷ ÷ ÷ + + ÷
¸ ¸ ¸ ¸
4 3 2 2 2
( ) – 4x – 16x – 12 2 2 3 4 2 2 3 4 f x x x x x x x x x ( ( = + = ÷ + ÷ + ÷ + + ÷
¸ ¸ ¸ ¸
4 3 2 2 2
( ) – 4x – 16x – 12 5 6 2 f x x x x x x x ( ( = + = ÷ + + ÷
¸ ¸ ¸ ¸
( )( ) ( ) ( )
2 2
5 6 3 2 , 2 2 1 x x x x x x x x ÷ + = ÷ ÷ + ÷ = + ÷
( ) ( ) ( ) ( )
4 3 2
( ) – 4x – 16x – 12 3 2 2 1 f x x x x x x x = + = ÷ ÷ + ÷
Roots of the equation
4 3 2
– 4x – 16x – 12 0. x x + =
3,2,2and 1